2019
DOI: 10.1128/jcm.01282-18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vitek MS for Differentiation of Cryptococcus neoformans and Cryptococcus gattii Genotypes

Abstract: Cryptococcus neoformans and Cryptococcus gattii are the main pathogenic species of invasive cryptococcosis among the Cryptococcus species. Taxonomic studies have shown that these two taxa have different genotypes or molecular types with biological and ecoepidemiological peculiarities. Matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) has been proposed as an alternative method for labor-intensive methods for C. neoformans and C. gattii genotype differentiation. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
2
4
0
2
Order By: Relevance
“…These results are in agreement with those shown in previous studies that report improved identification of Cryptococcus species based on MALDI-TOF MS and the implementation of extended in-house libraries: Firacative et al and Siqueira et al reported 100% correct molecular-type identifications [ 23 , 27 ] and Posteraro et al 98.8% unambiguous discrimination at the same level [ 28 ]. On the other hand, McTaggart et al also showed 98.8% species-level identification although in their case no interspecies hybrids were included in the study [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with those shown in previous studies that report improved identification of Cryptococcus species based on MALDI-TOF MS and the implementation of extended in-house libraries: Firacative et al and Siqueira et al reported 100% correct molecular-type identifications [ 23 , 27 ] and Posteraro et al 98.8% unambiguous discrimination at the same level [ 28 ]. On the other hand, McTaggart et al also showed 98.8% species-level identification although in their case no interspecies hybrids were included in the study [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…This goal was only fulfilled completely when peak analysis was performed and the three Cryptococcus species analyzed in this study distinctively clustered together. Other authors have provided species-level discrimination in 98.1-100% of the cases [21,23,27]. Although some of these studies were performed on higher number of isolates, our results also reflect the improvements made on the commercial database during the last years.…”
Section: Discussionsupporting
confidence: 73%
“…However, using the respective research only software (RUO), and particularly with complementation with in-house generated spectra, rapid and reliable identification is readily achieved. Furthermore, accurate identification of all the genotypes of C. neoformans and C. gattii has been reported [107,108,109].…”
Section: Diagnosismentioning
confidence: 99%